Les moteurs de la déforestation des mangroves urbaines du Grand Libreville (Gabon) - Marjolaine Okanga-Guay; Rogombe Laetitia Guylia; Ondo Assoumou Emmanuel; Lembe Bekale Aline; Akendengue Aken Igor; Mombo Jean-Bernard (VertigO, 2022)
Despite their importance to the stability and health of coastal environments, mangroves are under significant pressure, mostly from anthropogenic origins. The objectives are to measure the reduction of mangrove areas between 2007 and 2020 in the urban area of Greater Libreville (Gabon) and to identify the drivers of deforestation. To do this, two complementary methods were applied: an analysis of the land use dynamics of three characteristic sites, based on orthophotos of very high resolution provided by Maxar Technologies, and direct observations. Thus, between 2007 and 2020, land use changes in Okala-Angondjé, Lowé and Igoumié are mainly marked by the progression of buildings and their encroachment on vegetation. All sites have experienced a net mangrove regression: 35.6 ha in Okala-Angondjé, 46.9 ha in Lowé and 36.6 ha in Igoumié, resulting in an overall deforestation rate of 0.8%/year. Anthropogenic retreats represent 57% of the regressions in Okala-Angondjé, 96% in Lowé River and 78% in Igoumié area. The drivers of deforestation are multiple: residential expansions, installation of fishing districts, hotel or tourist establishments, creation and extension of garbage dumps, industrialization and port development and energy installations. Other economic activities (agriculture, livestock and aquaculture) have caused some deforestation of mangroves, but to a lesser extent. However, the annual rate of urban mangrove deforestation in Gabon's Estuary Province is higher than the mean rate of global mangrove deforestation.